Analisis Kesalahan Berbahasa Teks Deskripsi Kelas X-11 SMAN 2 Tasiknalaya dalam Kategori Linguistik - Widyanti Kusuma; Deri Ahmad Raihan; Fany Haifa Alia; Dias Sena Hidayat; Ai Siti Nurjamilah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This language error analysis aims to describe language errors in terms of phonology, morphology, syntax, semantics and spelling contained in descriptive texts made by X-11 students at SMAN 2 Tasikmalaya as well as providing corrections to these errors. The researcher used a descriptive analysis method by carrying out several stages in the research process, including: (1) collecting data, (2) describing the data, (3) analyzing the data, and (4) drawing conclusions. The research techniques used in this research are observation, interviews and literature studies or literature studies by conducting a review study of books, literature, notes and reports that are related to the problem being solved. The results of the analysis regarding language errors in descriptive texts made by X-11 students at SMAN 2 Tasikmalaya can be concluded that there are forms of language errors in the areas of phonology, morphology, syntax, semantics and spelling. Linguistic-morphological category errors include errors in affixation. Syntactic errors consist of errors in sentence construction. There are also semantic errors which consist of errors in the meaning of a sentence which can make the reader misinterpret the sentence. Then there are errors in the use of spelling or phonology, these spelling errors consist of spelling errors in usage and writing capital letters.